ANTIMICROBIAL SUSCEPTIBILITY OF INTRA-ABDOMINAL INFECTION ISOLATES FROM A TERTIARY CARE HOSPITAL IN KARACHI - Saad, Uzma; Anwar, Sana; Khara, Usman Zafar; Siddiqui, Maham; Saeed, Hina (Journal of Ayub Medical College Abbottabad, 2016)
Background: Intra-abdominal infections are associated with significant morbidity and mortality. The most frequent pathogens involved are the gastrointestinal flora which can cause poly-microbial infections. Microbiological diagnosis is required to determine the aetiology and antimicrobial susceptibility of the organisms involved. Prompt initiation of antimicrobials is essential for improving patient's outcome. Knowledge of local trends of antimicrobial resistance in nosocomial isolates is essential for empiric therapy. Methods: A total of 190 clinical isolates collected from intra-abdominal infections during July 2013 to July 2014 were included in the study. Organism identification and Antimicrobial sensitivity testing using standard biochemical tests and CLSI recommended criteria was carried out. Result: Of the total 190 isolates from abdominal infection sources 52% were from fluid sources (peritoneal & ascitic fluid), 41% were from gall bladder and 6.5% were from other abdominal sources. E. coli (46.8%) was the most frequently isolated gram negative and Enterococcus (13.1%) was the most frequently isolated gram positive organism. Carbapenem (imipenem) was the most active agent against enterobacteraceae exhibiting, 94.4% and 91.3% sensitivity against E. coli and Klebsiella respectively. While vancomycin was the most active agent against gram positive organisms. Eighty-four percent of the Enterococci isolated were sensitive to vancomycin. Most isolates exhibited resistance to one or more antibiotics. Conclusion: Continuous evolution of antimicrobial resistance patterns in bacteria necessitates updating of local data on antimicrobial susceptibility profiles to ensure the safety and efficacy of pathogen specific antimicrobial therapies. Keywords: Intra-abdominal infections (IAI), antimicrobials; resistant; sensitive